An Efficient Data Dissemination Method for VANET with the help of RSUs - N Sree Divya, Dr. Veeramallu Boddu (International Journal of Advanced Science and Technology, 2020)
There is a high demand for innovation in social issues during initial phase of VANET (Vehicular Ad-Hoc Network) technology. VANET is defined as prominent research area but it turned late in search key point in the wireless networking area. Routing is playing a crucial role in VANET technology. In VANET it is more responsible for Position based routing protocols, while contrasted with each other protocol. QoS (Quality of Service) is one required to develop many application for VANETs (Vehicle Ad-Hoc Networks). Due to its substantial mobility and high node density, here complexity of routing is increased enormously, which challenges the results in terms of QoS, security, and process of routing. Here in paper we propose a Road Side Unit based Discovery Procedure (RSUDP), which takes the advantage of using RSUs in VANET. In RSUDP, the RSUs acts as gateway to the network and the RSUs are interconnected with each other for data sharing. In RSUDP protocol, that have improved our model which gives improvement output comings like Throughput, End to End Delay, and packet delivery ratio (PDR). The significance of proposed routing protocol is represented based on the simulation and comparison results that improve the QoS. Keywords: VANET, RSU, Routing protocols, EH-GPSR, CL-ACO, QoS, AODV, RSUDP.